Responses to climate variability of the livestock sector in the north-west province, South Africa - Hudson, Jerry Wayne, author; Kathleen, Galvin, advisor; Smith, Freeman M. (Freeman Minson), 1939-, committee member; Magennis, Ann, committee member (Colorado State University. Libraries, 2002)
The goal of this study is to compare management drought strategies, including the use of climate forecasts, of livestock farmers in commercial areas with livestock farmers in adjacent communal areas within the western region of the North-West Province of the Republic of South Africa. In this rural semi-arid to arid region of the southern Kalahari, the majority of people make their living from animal production. It is shown that commercial farmers have a greater number of strategic options and greater accessibility to natural and human resources including pasture lands, water, and information. This research demonstrates that in this relatively homogeneous ecological setting, farmers' animal management responses to drought and use of climate forecasts are highly variable due to human factors such as culture, production goals, history, government policy, and market constraints. A human ecological framework is used to explain research findings and examine results within existing ecological, economic, ethnic, and historical constraints faced by local populations.
Department Head: Hennie Scholtz.